Determinants of Turnover Intention: The Role of Organizational Commitment, Job Satisfaction, and Job Stress at PT JNE Padang - Fesaraweny Fesaraweny; Rozi Destian; Habibah Muharmi; Windy Kususmahati (Jurnal Multidisiplin Sahombu, 2026)
Turnover intention is one of the human resource problems that are often faced by service companies, especially in the logistics industry which has a high level of work demands. This study aims to analyze the influence of organizational commitment, job satisfaction, and work stress on the turnover intention of PT JNE Padang employees. This study uses a quantitative approach with a survey method. Data was obtained through the distribution of questionnaires to 130 employees as research respondents. The data analysis technique used was multiple linear regression analysis with the help of SPSS software. The results of the study showed that partially organizational commitment had a negative and significant effect on turnover intention, while work stress had a positive and significant effect on turnover intention. Meanwhile, job satisfaction does not have a significant effect on turnover intention. Simultaneously, organizational commitment, job satisfaction, and work stress have a significant effect on the turnover intention of PT JNE Padang employees. These findings indicate that increasing organizational commitment and effective work stress management are important factors in reducing employee turnover intention. This research is expected to be a consideration for company management in formulating sustainable human resource management policies.